DIFFERENCES INDUSTRY PATTERNS BASED ON MILLENNIAL CUSTOMER PATH AT FAST FOOD RESTAURANTS - Archippus Christopher Hendra; Budi Setiawan; Agustina Shinta Hartati Wahyuningtyas (Socio-Economics/Agribusiness Department, 2022)
Marketing 4.0 forms a new customer path, which was previously 4A (aware, attitude, act, act again) to 5A (aware, appeal, ask, act, advocate). The main goal of the 4A is for customers to become loyal to a brand. However, in the 5A customer path, loyalty to a brand is not the primary goal but instead advertising or promoting the brand. This study aims to analyze industrial patterns formed based on customer lines at fast food restaurants in Malang City. This research approach uses a quantitative descriptive approach, which is carried out by collecting information about the picture of consumers in the research area. The results of the chi square H1 test were received, namely advocacy carried out by respondents aged 30-39 years not higher than respondents aged 20-29. The fast food restaurant industry pattern formed in the three restaurants in each age group (McDonald's, KFC, and Burger King) has the same shape: door knobs.